"Olha de novo": uma análise crítica do discurso publicitário da diversidade - Duarte, Thamires Rodrigues (2024)
In this study, advertising that adopts the discourse of diversity was addressed, mainly regarding race, gender and sexual orientation. The theoretical/methodological approach of Marxism was used, as well as Discourse Analysis (DA) techniques to carry out the process of investigating the context, added to the interpretation and analysis of qualitative material from three advertising pieces for the brands Avon, Natura and L 'the real. The ideological character of the appropriation of diversity discourse by the market was investigated, constructed through meaning strategies with verbal and non-verbal language in advertising.